Extrusion of sorghum, soybean meal, and whole soybeans improves growth performance and nutrient digestibility in finishing pigs - Gugle, Terry L.; Hines, Robert H.; Hancock, Joe D. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
One hundred forty-four finishing pigs (124 lb avg initial wt) were used to determine the effects of extruding sorghum, soybean meal (SBM), and whole soybeans on growth performance and nutrient digestibility. Treatments were: 1) control diet with ground sorghum, SBM, and soybean oil; 2) diet 1 with the ground sorghum, SBM, and soybean oil blended and extruded; 3) sorghum and whole soybeans extruded separately and blended; and 4) sorghum and extruded soybeans blended and extruded together. Extrusion was in an Insta-Pro extruder. All diets were formulated to be equal in concentrations of metabolizable energy (ME) and lysine. Pigs fed diets with extruded ingredients had improved F/G. Extrusion of sorghum and extruded soybeans together was of greater benefit than extruding those ingredients separately. Diets with extruded ingredients had greater digestibilities of DM and N, but fat thickness at the last rib was not affected by treatment. Overall, optimum nutrient digestibility was achieved by feeding extruded diet ingredients, and efficiency of gain was maximized by feeding an extruded blend of sorghum and whole soybeans.
Keywords: Swine; GF; Process; Sorghum; Soybeans; Performance; Digestibility